Research of Lurication Characteristic of Mechanical Parts in Higher Pair Contact based on Longitudinal Roughness Texture - Feng Nan; Qi Xiumei; Gao Chuangkuan (Jixie chuandong)
The surface roughness data of a disc with longitudinal roughness texture is measured by a roughness profile measuring analyzer firstly. With the help of the nonlinear Fourier transform,the measured data is used to form a roughness function which is then added to the oil film thickness equation and a model of mixed Elastohydrodynamic lubrication for a pair of mechanical parts in higher pair contact is established. Based on this model,45 groups numerical calculations are carried through changing lubricant viscosities. The computing results show that the average oil film thickness for rough surfaces is smaller than the corresponding value for smooth surface. But the two tend to consistent when the film ratio exceeds a specific value. As the viscosity increases,the maximum value of contact stress on rough surface decreases gradually,but it is always greater than the corresponding value for smooth surface contact. However,the both are less than the corresponding Hertz stress regardless of rough or smooth surface contact,which indicates once again that a scientific lubrication is very helpful for increasing the contact fatigue life of mechanical parts.